‘Power to the Convicted Class’: Re-Assessing Prisoner-Led Movements and Trade Union Organizing - Behan, Cormac (The British journal of criminology, 2025)
This article examines prisoner-led movements that have sought the right to representation and improvements in pay and conditions. We argue that this strand of prison organizing has tended to be subsumed into narratives around prison disturbances, studies of movements for prisoners’ rights and campaigns for penal reform. The article considers the extent to which prisoner-led organizations have adapted to their unique set of circumstances by examining some historical and contemporary examples of labour organizing in prison. We contend that questions of class and class analysis more widely in relation to prisoner labour have not been explicitly analysed within contemporary penology, and consider the need for a new approach to critique worker organizing within prison settings.